A coated mirror and a method of making the same

CN122876757APending Publication Date: 2026-10-09DONGGUAN YUKUN NANO INJECTION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611053406.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0002]传统反光镜通常采用普通玻璃或钢化玻璃为基体,在玻璃背面通过镀银或镀铝工艺形成反射层,再以漆料保护金属层,最终得到反射镜产品;但是,现有技术中反光镜用胶粘剂主要为丙烯酸压敏胶,丙烯酸压敏胶耐候性较差,在长期紫外照射和湿热环境下易黄变,导致透光率下降

Benefits of technology

1、本发明制备的异氰酸酯固化剂中含有氟烷基链和二苯甲酮基团,氟烷基链一方面具有较好的耐候性,另一方面折射率低,使用时可降低胶粘剂整体的折射率,在一定程度上提高胶粘剂的透光率;二苯甲酮基团可吸收紫外光,避免长期紫外辐照下胶粘剂黄变,性能下降,维持高透光率;此外,异佛尔酮二异氰酸酯为椅式结构,具有不对称分子链,因此,胶粘剂不易结晶,与氟烷基链协同,可进一步提高胶粘剂的透光率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure REF-OBJ-1784105207865-000001
    Figure REF-OBJ-1784105207865-000001
Patent Text Reader

Abstract

The application discloses a coated reflector and a preparation method thereof, and relates to the technical field of reflectors.The application prepares an adhesive containing a hydroxyl acrylate glue solution, an isocyanate curing agent and a macromolecular antioxidant.The isocyanate curing agent contains a fluorine alkyl chain and a benzophenone group, has good weather resistance and low refractive index, the macromolecular antioxidant contains a benzophenone and a fluorine alkyl chain, and the chemical stability of the macromolecule is better than that of a small molecule.The prepared adhesive is applied to the coated reflector, the high light transmittance, the moisture and heat aging resistance and the ultraviolet aging resistance of the adhesive are utilized, the problems, such as yellowing and failure of a traditional acrylate adhesive under ultraviolet irradiation and in a moisture and heat environment, are solved, delamination or blistering does not occur in long-term use, and the service life of the coated reflector is comprehensively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of reflector technology, specifically a coated reflector and its preparation method. Background Technology

[0002] Traditional reflectors typically use ordinary glass or tempered glass as the base material, with a reflective layer formed on the back of the glass through silver or aluminum plating. Then, a metal layer is protected with paint to finally obtain the reflector product. However, the adhesive used for reflectors in the current technology is mainly acrylic pressure-sensitive adhesive. Acrylic pressure-sensitive adhesive has poor weather resistance and is prone to yellowing under long-term ultraviolet radiation and humid and hot environments, resulting in a decrease in light transmittance.

[0003] Patent CN111454396A discloses a weather-resistant polyacrylate emulsion and its preparation method. The weather-resistant polyacrylate emulsion is prepared by free radical polymerization of monoalkenylpentylcycloboronium hexadecane with monomers containing olefin bonds such as acrylate and styrene. It has good weather resistance and bonding strength, but does not explain the light transmittance of the adhesive.

[0004] Therefore, this invention proposes a coated reflector and its preparation method, which solves the above-mentioned problems by preparing an adhesive with good weather resistance and high light transmittance. Summary of the Invention

[0005] The purpose of this invention is to provide a coated reflector and its preparation method to solve the problems raised in the prior art.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a coated reflector, comprising, from bottom to top, a glass substrate, an adhesive layer, a masking ink layer, a metal layer, a thin film substrate layer, and a surface hardening layer; The adhesive layer is obtained by coating and curing with an adhesive. The adhesive comprises the following components: hydroxy acrylate adhesive, isocyanate curing agent, and macromolecular antioxidant.

[0007] A method for preparing a coated reflector includes the following steps: Step 1: Take a glass substrate, apply adhesive to one side of its surface to form an adhesive layer, apply masking ink to the surface of the adhesive layer, and cure to form a masking ink layer; Step 2: Deposit a metal target on the surface of the masking ink layer to form a metal layer, then set a thin film on the surface of the metal layer to form a thin film substrate layer, and finally coat the surface of the thin film substrate layer with a hard coating liquid and cure it to form a surface hardened layer, thus obtaining a coated reflector.

[0008] Furthermore, in step 1, the thickness of the glass substrate is 1~3mm; The thickness of the adhesive layer is 25~50μm; The thickness of the masking ink layer is 5~30μm.

[0009] Furthermore, in step 1, the curing process conditions are: temperature 50~70℃, time 3~5h.

[0010] Furthermore, in step 2, the metal layer is obtained by using a metal target and depositing it through magnetron sputtering or vacuum evaporation. The metal target material is one of Al (aluminum), Ag (silver), and Cr (chromium).

[0011] Furthermore, when magnetron sputtering is used, the process conditions are: under argon atmosphere protection, sputtering power of 120~160W, sputtering time of 4~8min; When vacuum evaporation is used, the process conditions are as follows: under argon atmosphere protection, evaporation current: 80~100A, evaporation time: 60~240s, evaporation boat temperature: 1000~1200℃.

[0012] Furthermore, in step 2, the thickness of the metal layer is 50~200nm; Furthermore, in step 2, the film is one of PET film (polyethylene terephthalate) or PC (polycarbonate) film; The thickness of the film is 120~250μm.

[0013] Furthermore, in step 2, the curing process conditions are: temperature 60~75℃, time 3~8min; The thickness of the surface hardening layer is 2~10μm.

[0014] Furthermore, the adhesive comprises the following components by weight: 80-100 parts hydroxy acrylate adhesive, 15-35 parts isocyanate curing agent, and 1-3 parts macromolecular antioxidant.

[0015] Furthermore, the preparation process of the hydroxyacrylate adhesive is as follows: Mix half of the mass of the mixed solution with the initiator, stir at room temperature under inert gas protection, and then heat up to react. After the reaction is completed, add the remaining mixed solution within 1.5~2.0h, keep the temperature and react to obtain hydroxy acrylate resin.

[0016] Furthermore, the mixed solution is obtained by mixing acrylic acid, hydroxyethyl acrylate, butyl acrylate, vinyl acetate and solvent in a mass ratio of (2~5):(16~20):(42~50):(24~32):(70~100).

[0017] Furthermore, the solvent is ethyl acetate; The initiator is azobisisobutyronitrile.

[0018] Furthermore, the inert gas is nitrogen.

[0019] Furthermore, the mass ratio of the mixed solution to the initiator is 100:(0.5~1.5).

[0020] Furthermore, the process conditions for stirring at room temperature are: temperature 20~30℃, rotation speed 150~200r / min, and time 20~30min; The process conditions for the heating reaction are: temperature 72~78℃, time 10~15min; The process conditions for the heat preservation reaction are: temperature 72~78℃, time 3.0~4.0h.

[0021] Furthermore, the rotation speeds for both the heating and holding reactions are the same as those for stirring at room temperature.

[0022] Furthermore, the preparation process of the isocyanate curing agent is as follows: S1: Mix anhydrous ethanol and N,N'-bis(2-hydroxyethyl)ethylenediamine, stir until homogeneous, then add hexafluorobutyl methacrylate, stir at room temperature and react, then add 4-propenoxy-2-hydroxybenzophenone, stir at room temperature and react, and after the reaction is complete, distill to obtain functionalized polyol. S2: Under inert gas protection, isophorone diisocyanate, functionalized polyol and dibutyltin dilaurate are mixed, heated and stirred to react, and an isocyanate curing agent is obtained.

[0023] Furthermore, in S1, the ratio of anhydrous ethanol, N,N'-bis(2-hydroxyethyl)ethylenediamine, hexafluorobutyl methacrylate, and 4-propenoxy-2-hydroxybenzophenone is 150 mL: (46~52) g: (80~90) g: (83~95) g.

[0024] Furthermore, in S1, the process conditions for the room temperature stirring reaction are: temperature 20~30℃, rotation speed 80~120r / min, and time 12~16h; In S1, the distillation process conditions are: temperature 60~65℃, time 40~50min.

[0025] Furthermore, in S2, the mass ratio of isophorone diisocyanate, functionalized polyol and dibutyltin dilaurate is (54~62):90:(0.030~0.035).

[0026] Furthermore, in S2, the process conditions for heating and stirring reaction are: temperature 60~80℃, rotation speed 100~150r / min, and time 2~4h.

[0027] Furthermore, in S2, the inert gas is nitrogen.

[0028] In the above technical solution, firstly, a secondary amino group of N,N'-bis(2-hydroxyethyl)ethylenediamine undergoes a Michael addition reaction with the unsaturated double bond of hexafluorobutyl methacrylate. Then, 4-propenoxy-2-hydroxybenzophenone is added, causing another secondary amino group of N,N'-bis(2-hydroxyethyl)ethylenediamine to react with the double bond of 4-propenoxy-2-hydroxybenzophenone, retaining the hydroxyl group, to obtain a functionalized polyol. Subsequently, the hydroxyl group of the functionalized polyol undergoes an addition reaction with the isocyanate group of isophorone diisocyanate, controlling the excess of isophorone diisocyanate to obtain an isocyanate-terminated compound, i.e., an isocyanate curing agent.

[0029] Furthermore, the preparation process of the macromolecular antioxidant is as follows: Step A: Under inert gas protection, 4-pentenoic acid, functionalized polyol, anhydrous dichloromethane and polymerization inhibitor are mixed and reacted in an ice bath. After the reaction is completed, an activator is added within 5-10 minutes, followed immediately by a catalyst. The reaction is heated and then filtered, washed and dried to obtain the functionalized antioxidant. Step B: Under inert gas protection, the functionalized antioxidant, N-phenylmaleimide, solvent and initiator are mixed and heated to react, then the temperature is increased to react again. After the reaction is completed, the mixture is distilled under reduced pressure to obtain the macromolecular antioxidant.

[0030] Furthermore, in step A, the ratio of 4-pentenoic acid, functionalized polyol, anhydrous dichloromethane, polymerization inhibitor, activator, and catalyst is (1.2~1.8) g : (0.5~1.0) g : 50 mL : (0.005~0.010) g : (12~18) mL : (0.10~0.15) g; The polymerization inhibitor is p-methoxyphenol; The activator was obtained by mixing N,N'-dicyclohexylcarbodiimide and anhydrous dichloromethane at a ratio of (2.8~3.2) g: 40 mL; The catalyst is 4-dimethylaminopyridine.

[0031] Furthermore, in step A, the process conditions for the ice bath reaction are: temperature 0~5℃, time 25~35min; The process conditions for the heating reaction are: temperature 32~38℃, time 12~15h.

[0032] Furthermore, in step A, the drying process conditions are: temperature 50~60℃, time 4~6h.

[0033] Furthermore, in step B, the ratio of functionalized antioxidant, N-phenylmaleimide, solvent, and initiator is (3.4~4.0) g : (1.5~2.0) g : 40 mL : (0.08~0.12) g; The solvent is cyclohexanone; The initiator is azobisisobutyronitrile.

[0034] Furthermore, in step B, the process conditions for the heating reaction are: temperature 72~78℃, time 25~35min; In step B, the process conditions for the heating reaction are: temperature 95~105℃, time 2.0~2.5h.

[0035] Furthermore, in step B, the process conditions for vacuum distillation are: temperature 85~95℃, time 20~35min.

[0036] Furthermore, in steps A and B, the inert gas is nitrogen.

[0037] In the above technical solution, the carboxyl group of 4-pentenoic acid is first esterified with the hydroxyl group of the functionalized polyol, retaining benzophenone and fluoroalkyl chains, while introducing double bonds to obtain a functionalized antioxidant; then, the double bonds of the functionalized antioxidant are used to perform free radical copolymerization with N-phenylmaleimide to obtain a macromolecular antioxidant.

[0038] Compared with the prior art, the beneficial effects of the present invention are: 1. The isocyanate curing agent prepared by this invention contains fluoroalkyl chains and benzophenone groups. On the one hand, the fluoroalkyl chains have good weather resistance, and on the other hand, they have a low refractive index, which can reduce the overall refractive index of the adhesive during use and improve the light transmittance of the adhesive to a certain extent. The benzophenone groups can absorb ultraviolet light, avoid yellowing and performance degradation of the adhesive under long-term ultraviolet irradiation, and maintain high light transmittance. In addition, isophorone diisocyanate has a chair structure and an asymmetric molecular chain, so the adhesive is not easy to crystallize. In synergy with the fluoroalkyl chains, it can further improve the light transmittance of the adhesive.

[0039] 2. The macromolecular antioxidant prepared by this invention contains benzophenone and fluoroalkyl chains. N-phenylmaleimide has good heat resistance. The three work synergistically to resist heat aging and UV aging, further improving the weather resistance of the adhesive. At the same time, the macromolecular structure has more stable chemical properties, preventing the functionalized antioxidant from self-polymerizing in the system, which would lead to a decline in the performance of the adhesive.

[0040] 3. The macromolecular antioxidant and isocyanate curing agent prepared in this invention both contain benzophenone and fluoroalkyl chains. When the two are compounded, they have good compatibility, are not prone to phase separation, and are not prone to forming light scattering interfaces, which can ensure high reflection efficiency and further improve the light transmittance of the adhesive. In addition, the adhesive prepared by this invention has good light transmittance and weather resistance, which can solve the problems of yellowing and failure of traditional acrylic adhesives under ultraviolet radiation and humid heat, and ensure that no delamination or blistering occurs during long-term use, thus comprehensively improving the service life of the coated reflector. Detailed Implementation

[0041] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0042] In the following specific implementation; The glass substrate is 3mm thick. Masking ink, model number SSRL-913; Optical transparent adhesive, part number DC184; The metal target material is aluminum, with a purity of 99.9%. The film is a PET film with a thickness of 200μm; Hard coating liquid, model number HS-CY300U.

[0043] Example 1: A method for preparing a coated reflector, comprising the following steps: (1) Preparation of hydroxyacrylate adhesive: Acrylic acid, hydroxyethyl acrylate, butyl acrylate, vinyl acetate and ethyl acetate were mixed in a mass ratio of 5:20:50:32:100 to obtain a mixed solution; Half of the mass fraction of the mixed solution was mixed with azobisisobutyronitrile (AIBN). Under a nitrogen atmosphere, the mixture was stirred at 200 rpm for 30 min at 30 °C. The temperature was then increased to 78 °C at the same speed for 15 min. After the reaction was completed, the remaining mixed solution was added within 2.0 h, and the mixture was kept at 78 °C at the same speed for 4.0 h to obtain a hydroxy acrylate adhesive. The mass ratio of the mixed solution to AIBN was 100:1.5. (2) Preparation of isocyanate curing agent: S1: Anhydrous ethanol and N,N'-bis(2-hydroxyethyl)ethylenediamine were mixed and stirred until homogeneous. Then, hexafluorobutyl methacrylate was added, and the mixture was stirred at 120 r / min for 16 h at 30 °C. Then, 4-propenoxy-2-hydroxybenzophenone was added, and the mixture was stirred at 120 r / min for 16 h. After the reaction was completed, the mixture was distilled at 65 °C for 50 min to obtain the functionalized polyol. In S1, the ratio of anhydrous ethanol, N,N'-bis(2-hydroxyethyl)ethylenediamine, hexafluorobutyl methacrylate, and 4-propenoxy-2-hydroxybenzophenone was 150 mL: 52 g: 90 g: 95 g. S2: Under nitrogen atmosphere protection, isophorone diisocyanate, functionalized polyol and dibutyltin dilaurate are mixed in a mass ratio of 62:90:0.035, heated to 80℃, and stirred at 150 r / min for 4 h to obtain isocyanate curing agent. (3) Preparation of macromolecular antioxidants: Step A: Under a nitrogen atmosphere, 4-pentenoic acid, functionalized polyol, anhydrous dichloromethane, and p-methoxyphenol were mixed and reacted in an ice bath at 5°C for 35 min. After the reaction was completed, an activator was added within 10 min, followed immediately by 4-dimethylaminopyridine. The mixture was heated to 38°C and reacted for 15 h. After the reaction was completed, the mixture was filtered, washed, and dried at 60°C for 6 h to obtain the functionalized antioxidant. In Step A, the ratio of 4-pentenoic acid, functionalized polyol, anhydrous dichloromethane, p-methoxyphenol, activator, and 4-dimethylaminopyridine was 1.8 g: 1.0 g: 50 mL: 0.010 g: 18 mL: 0.15 g. The activator was obtained by mixing N,N'-dicyclohexylcarbodiimide and anhydrous dichloromethane at a ratio of 3.2 g: 40 mL. Step B: Under a nitrogen atmosphere, functionalized antioxidant, N-phenylmaleimide, cyclohexanone and azobisisobutyronitrile were mixed at a ratio of 4.0 g: 2.0 g: 40 mL: 0.12 g, heated to 78 °C and reacted for 35 min, then heated to 105 °C and reacted for 2.5 h. After the reaction was completed, the mixture was distilled under reduced pressure at 95 °C for 35 min to obtain a macromolecular antioxidant. (4) Preparation of coated mirrors: Step 1: Take a glass substrate, coat one side of it with adhesive to form a 50μm adhesive layer, coat the adhesive layer with masking ink, and cure at 70℃ for 5h to form a 30μm masking ink layer; the adhesive includes the following components by weight: 100 parts hydroxy acrylate adhesive, 35 parts isocyanate curing agent, and 3 parts macromolecular antioxidant. Step 2: Aluminum target material is magnetron sputtered onto the surface of the masking ink layer to form a 200nm metal layer. Then, a PET film is deposited on the surface of the metal layer to form a 200μm thin film substrate layer. Finally, a hard coating liquid is coated on the surface of the thin film substrate layer and cured at 75℃ for 8 minutes to form a 10μm surface hardened layer, thus obtaining the coated reflector. The magnetron sputtering process conditions are: sputtering power of 160W and sputtering time of 8 minutes under argon atmosphere protection.

[0044] Example 2: A method for preparing a coated reflector, comprising the following steps: (1) Preparation of hydroxyacrylate adhesive: Acrylic acid, hydroxyethyl acrylate, butyl acrylate, vinyl acetate and ethyl acetate were mixed in a mass ratio of 3:18:46:28:85 to obtain a mixed solution. Half of the mass fraction of the mixed solution was mixed with azobisisobutyronitrile (AIBN). Under a nitrogen atmosphere, the mixture was stirred at 175 r / min for 25 min at 25 °C. The temperature was then increased to 76 °C at the same speed and reacted for 13 min. After the reaction was completed, the remaining mixed solution was added within 1.8 h, and the mixture was kept at 76 °C at the same speed and reacted for 3.5 h to obtain a hydroxy acrylate adhesive. The mass ratio of the mixed solution to AIBN was 100:1.0. (2) Preparation of isocyanate curing agent: S1: Anhydrous ethanol and N,N'-bis(2-hydroxyethyl)ethylenediamine were mixed and stirred until homogeneous. Then, hexafluorobutyl methacrylate was added, and the mixture was stirred at 100 r / min for 14 h at 25 °C. Then, 4-propenoxy-2-hydroxybenzophenone was added, and the mixture was stirred at 100 r / min for 14 h. After the reaction was completed, the mixture was distilled at 63 °C for 45 min to obtain the functionalized polyol. In S1, the ratio of anhydrous ethanol, N,N'-bis(2-hydroxyethyl)ethylenediamine, hexafluorobutyl methacrylate, and 4-propenoxy-2-hydroxybenzophenone was 150 mL: 50 g: 85 g: 90 g. S2: Under nitrogen atmosphere protection, isophorone diisocyanate, functionalized polyol and dibutyltin dilaurate are mixed in a mass ratio of 58:90:0.033, heated to 70°C, and stirred at 130 r / min for 3 h to obtain isocyanate curing agent. (3) Preparation of macromolecular antioxidants: Step A: Under a nitrogen atmosphere, 4-pentenoic acid, functionalized polyol, anhydrous dichloromethane, and p-methoxyphenol were mixed and reacted in an ice bath at 3°C ​​for 30 min. After the reaction was completed, an activator was added within 8 min, followed immediately by 4-dimethylaminopyridine. The mixture was heated to 36°C and reacted for 13 h. After the reaction was completed, the mixture was filtered, washed, and dried at 55°C for 5 h to obtain the functionalized antioxidant. In Step A, the ratio of 4-pentenoic acid, functionalized polyol, anhydrous dichloromethane, p-methoxyphenol, activator, and 4-dimethylaminopyridine was 1.6 g: 0.8 g: 50 mL: 0.008 g: 16 mL: 0.13 g. The activator was obtained by mixing N,N'-dicyclohexylcarbodiimide and anhydrous dichloromethane at a ratio of 3.0 g: 40 mL. Step B: Under a nitrogen atmosphere, functionalized antioxidant, N-phenylmaleimide, cyclohexanone and azobisisobutyronitrile were mixed at a ratio of 3.8g:1.8g:40mL:0.10g, heated to 76℃ and reacted for 30min, then heated to 100℃ and reacted for 2.3h. After the reaction was completed, the mixture was distilled under reduced pressure at 90℃ for 30min to obtain a macromolecular antioxidant. (4) Preparation of coated mirrors: Step 1: Take a glass substrate and apply adhesive to one side of it to form a 40μm adhesive layer. Apply masking ink to the surface of the adhesive layer and cure at 60℃ for 4 hours to form a 15μm masking ink layer. The adhesive includes the following components by weight: 90 parts hydroxyl acrylate adhesive, 25 parts isocyanate curing agent, and 2 parts macromolecular antioxidant. Step 2: Aluminum target material is magnetron sputtered onto the surface of the masking ink layer to form a 125nm metal layer. Then, a PET film is deposited on the surface of the metal layer to form a 200μm thin film substrate layer. Finally, a hard coating liquid is coated on the surface of the thin film substrate layer and cured at 70℃ for 5min to form a 6μm surface hardened layer, thus obtaining the coated reflector. The magnetron sputtering process conditions are: sputtering power of 140W and sputtering time of 6min under argon atmosphere protection.

[0045] Example 3: A method for preparing a coated reflector, comprising the following steps: (1) Preparation of hydroxyacrylate adhesive: Acrylic acid, hydroxyethyl acrylate, butyl acrylate, vinyl acetate and ethyl acetate were mixed in a mass ratio of 2:16:42:24:70 to obtain a mixed solution; Half of the mass fraction of the mixed solution was mixed with azobisisobutyronitrile (AIBN). Under a nitrogen atmosphere, the mixture was stirred at 150 rpm for 20 min at 20 °C. The temperature was then raised to 72 °C at the same speed and reacted for 10 min. After the reaction was completed, the remaining mixed solution was added within 1.5 h, and the mixture was kept at 72 °C at the same speed and reacted for 3.0 h to obtain a hydroxy acrylate adhesive. The mass ratio of the mixed solution to AIBN was 100:0.5. (2) Preparation of isocyanate curing agent: S1: Anhydrous ethanol and N,N'-bis(2-hydroxyethyl)ethylenediamine were mixed and stirred until homogeneous. Then, hexafluorobutyl methacrylate was added, and the mixture was stirred at 80 r / min for 12 h at 20 °C. Then, 4-propenoxy-2-hydroxybenzophenone was added, and the mixture was stirred at 80 r / min for 12 h. After the reaction was completed, the mixture was distilled at 60 °C for 40 min to obtain the functionalized polyol. In S1, the ratio of anhydrous ethanol, N,N'-bis(2-hydroxyethyl)ethylenediamine, hexafluorobutyl methacrylate, and 4-propenoxy-2-hydroxybenzophenone was 150 mL: 46 g: 80 g: 83 g. S2: Under nitrogen atmosphere protection, isophorone diisocyanate, functionalized polyol and dibutyltin dilaurate are mixed in a mass ratio of 54:90:0.030, heated to 60℃, and stirred at 100r / min for 2h to obtain isocyanate curing agent. (3) Preparation of macromolecular antioxidants: Step A: Under a nitrogen atmosphere, 4-pentenoic acid, functionalized polyol, anhydrous dichloromethane, and p-methoxyphenol were mixed and reacted in an ice bath at 0°C for 25 min. After the reaction was completed, an activator was added within 5 min, followed immediately by 4-dimethylaminopyridine. The mixture was heated to 32°C and reacted for 12 h. After the reaction was completed, the mixture was filtered, washed, and dried at 50°C for 4 h to obtain the functionalized antioxidant. In Step A, the ratio of 4-pentenoic acid, functionalized polyol, anhydrous dichloromethane, p-methoxyphenol, activator, and 4-dimethylaminopyridine was 1.2 g: 0.5 g: 50 mL: 0.005 g: 12 mL: 0.10 g. The activator was obtained by mixing N,N'-dicyclohexylcarbodiimide and anhydrous dichloromethane at a ratio of 2.8 g: 40 mL. Step B: Under a nitrogen atmosphere, functionalized antioxidant, N-phenylmaleimide, cyclohexanone and azobisisobutyronitrile were mixed at a ratio of 3.4g:1.5g:40mL:0.08g, heated to 72℃ and reacted for 25min, then heated to 95℃ and reacted for 2.0h. After the reaction was completed, the mixture was distilled under reduced pressure at 85℃ for 20min to obtain a macromolecular antioxidant. (4) Preparation of coated mirrors: Step 1: Take a glass substrate and apply adhesive to one side of it to form a 25μm adhesive layer. Apply masking ink to the surface of the adhesive layer and cure at 50℃ for 3 hours to form a 5μm masking ink layer. The adhesive includes the following components by weight: 80 parts hydroxyl acrylate adhesive, 15 parts isocyanate curing agent, and 1 part macromolecular antioxidant. Step 2: Aluminum target material is magnetron sputtered onto the surface of the masking ink layer to form a 50 μm metal layer. Then, a PET film is deposited on the surface of the metal layer to form a 200 μm thin film substrate layer. Finally, a hard coating liquid is coated on the surface of the thin film substrate layer and cured at 60°C for 3 min to form a 2 μm surface hardened layer, thus obtaining the coated reflector. The magnetron sputtering process conditions are: sputtering power of 120 W and sputtering time of 4 min under argon atmosphere protection.

[0046] Comparative Example 1: Compared with Example 1, the isocyanate curing agent was replaced with isophorone diisocyanate, and all other conditions remained the same as in Example 1. Specifically: (1) Preparation of hydroxy acrylate adhesive: Same as in Example 1; (2) Preparation of macromolecular antioxidants: Same as in Example 1; (3) Preparation of coated mirrors: Step 1: Take a glass substrate and apply an adhesive to one side of it to form a 50μm adhesive layer. Apply a masking ink to the surface of the adhesive layer and cure it at 70℃ for 5 hours to form a 30μm masking ink layer. The adhesive includes the following components by weight: 100 parts hydroxy acrylate liquid, 35 parts isophorone diisocyanate, and 3 parts macromolecular antioxidant. Step 2: Aluminum target material is magnetron sputtered onto the surface of the masking ink layer to form a 200nm metal layer. Then, a PET film is deposited on the surface of the metal layer to form a 200μm thin film substrate layer. Finally, a hard coating liquid is coated on the surface of the thin film substrate layer and cured at 75℃ for 8 minutes to form a 10μm surface hardened layer, thus obtaining the coated reflector. The magnetron sputtering process conditions are: sputtering power of 160W and sputtering time of 8 minutes under argon atmosphere protection.

[0047] Comparative Example 2: Compared with Example 1, a functionalized antioxidant was directly added to the hydroxy acrylate adhesive, with all other conditions remaining unchanged as in Example 1. Specifically: (1) Preparation of hydroxy acrylate adhesive: Same as in Example 1; (2) Preparation of isocyanate curing agent: Same as in Example 1; (3) Preparation of functionalized antioxidants: Under a nitrogen atmosphere, 4-pentenoic acid, functionalized polyol, anhydrous dichloromethane, and p-methoxyphenol were mixed and reacted in an ice bath at 5°C for 35 min. After the reaction was completed, an activator was added within 10 min, followed immediately by 4-dimethylaminopyridine. The mixture was heated to 38°C and reacted for 15 h. After the reaction was completed, the mixture was filtered, washed, and dried at 60°C for 6 h to obtain the functionalized antioxidant. The ratio of 4-pentenoic acid, functionalized polyol, anhydrous dichloromethane, p-methoxyphenol, activator, and 4-dimethylaminopyridine was 1.8 g: 1.0 g: 50 mL: 0.010 g: 18 mL: 0.15 g. The activator was prepared by mixing N,N'-dicyclohexylcarbodiimide and anhydrous dichloromethane at a ratio of 3.2 g: 40 mL. (4) Preparation of coated mirrors: Step 1: Take a glass substrate, coat one side of it with adhesive to form a 50μm adhesive layer, coat the adhesive layer with masking ink, and cure at 70℃ for 5h to form a 30μm masking ink layer; the adhesive includes the following components by weight: 100 parts hydroxy acrylate adhesive, 35 parts isocyanate curing agent, and 3 parts functionalized antioxidant. Step 2: Aluminum target material is magnetron sputtered onto the surface of the masking ink layer to form a 200nm metal layer. Then, a PET film is deposited on the surface of the metal layer to form a 200μm thin film substrate layer. Finally, a hard coating liquid is coated on the surface of the thin film substrate layer and cured at 75℃ for 8 minutes to form a 10μm surface hardened layer, thus obtaining the coated reflector. The magnetron sputtering process conditions are: sputtering power of 160W and sputtering time of 8 minutes under argon atmosphere protection.

[0048] Comparative Example 3: Compared with Example 1, the macromolecular antioxidant was replaced with antioxidant 1135, and all other conditions remained the same as in Example 1. Specifically: (1) Preparation of hydroxy acrylate adhesive: Same as in Example 1; (2) Preparation of isocyanate curing agent: Same as in Example 1; (3) Preparation of coated mirrors: Step 1: Take a glass substrate and apply adhesive to one side of it to form a 50μm adhesive layer. Apply masking ink to the surface of the adhesive layer and cure at 70℃ for 5 hours to form a 30μm masking ink layer. The adhesive includes the following components by weight: 100 parts hydroxy acrylate adhesive, 35 parts isocyanate curing agent, and 3 parts antioxidant 1135. Step 2: Aluminum target material is magnetron sputtered onto the surface of the masking ink layer to form a 200nm metal layer. Then, a PET film is deposited on the surface of the metal layer to form a 200μm thin film substrate layer. Finally, a hard coating liquid is coated on the surface of the thin film substrate layer and cured at 75℃ for 8 minutes to form a 10μm surface hardened layer, thus obtaining the coated reflector. The magnetron sputtering process conditions are: sputtering power of 160W and sputtering time of 8 minutes under argon atmosphere protection.

[0049] Comparative Example 4: Compared with Example 1, the adhesive was replaced with an optically transparent adhesive, and all other conditions remained the same as in Example 1. Specifically: Step 1: Take a glass substrate, coat one side of it with optically transparent adhesive to form a 50μm adhesive layer, coat the adhesive layer with masking ink, and cure at 70℃ for 5h to form a 30μm masking ink layer. Step 2: Aluminum target material is magnetron sputtered onto the surface of the masking ink layer to form a 200nm metal layer. Then, a PET film is deposited on the surface of the metal layer to form a 200μm thin film substrate layer. Finally, a hard coating liquid is coated on the surface of the thin film substrate layer and cured at 75℃ for 8 minutes to form a 10μm surface hardened layer, thus obtaining the coated reflector. The magnetron sputtering process conditions are: sputtering power of 160W and sputtering time of 8 minutes under argon atmosphere protection.

[0050] experiment: Transmittance test: Referring to GB / T 2410-2008, the adhesives obtained in the examples and comparative examples were made into 50×50mm samples, and the transmittance of the samples was tested to characterize their transmittance performance. Adhesion performance test: The adhesive strength was tested using an electronic tensile testing machine to characterize its adhesion performance, with a tensile rate of 500 mm / min. UV resistance test: The adhesive was placed at 1000W / m 2 After being irradiated with ultraviolet light for 200 hours, its light transmittance and adhesion properties were tested. Heat resistance test: After placing the adhesive in an environment of 70℃ and 60% relative humidity for 7 days, its light transmittance and bonding performance are tested.

[0051] Based on the data in the table above, the following conclusions can be drawn: Compared with Example 1, Comparative Example 1 replaced the isocyanate curing agent with isophorone diisocyanate. The light transmittance and bonding strength after UV aging test and heat aging test decreased. This is because the isocyanate curing agent contains fluoroalkyl chains and benzophenone groups. On the one hand, the fluoroalkyl chains have good weather resistance, and on the other hand, the benzophenone groups have a low refractive index. The benzophenone groups can absorb ultraviolet light and avoid the adhesive from yellowing and degrading under long-term ultraviolet irradiation. Compared with Example 1, Comparative Example 2 directly added functionalized antioxidants to the hydroxy acrylate adhesive. After UV aging test, the performance did not decrease significantly, but after heat aging test, the performance decreased significantly. This is because N-phenylmaleimide has good heat resistance and plays an anti-heat aging role. Compared with Example 1, Comparative Example 3 replaced the macromolecular antioxidant with antioxidant 1135. The performance degradation after heat aging was greater than that after UV aging. This is because both the macromolecular antioxidant and the isocyanate curing agent contain benzophenone and fluoroalkyl chains. However, the macromolecular antioxidant also contains N-phenylmaleimide. After replacing it with antioxidant 1135, the heat resistance decreased. Compared with Example 1, Comparative Example 4 replaced the adhesive with an optically transparent adhesive, and all properties decreased. In summary, the isocyanate curing agent and macromolecular antioxidant prepared in this invention can promote the comprehensive improvement of the light transmittance, bonding strength, UV resistance and heat resistance of the prepared adhesive.

[0052] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

Claims

1. A coated reflector, characterized in that: From bottom to top, it includes a glass substrate, an adhesive layer, a masking ink layer, a metal layer, a thin film substrate layer, and a surface hardening layer. The adhesive layer is obtained by coating and curing with an adhesive. The adhesive comprises the following components: hydroxy acrylate adhesive, isocyanate curing agent, and macromolecular antioxidant; The isocyanate curing agent contains fluoroalkyl chains and benzophenone groups.

2. A method for preparing a coated reflector, characterized in that: Includes the following steps: Step 1: Take a glass substrate, apply adhesive to one side of its surface to form an adhesive layer, apply masking ink to the surface of the adhesive layer, and cure to form a masking ink layer; Step 2: Deposit a metal target on the surface of the masking ink layer to form a metal layer, then set a thin film on the surface of the metal layer to form a thin film substrate layer, and finally coat the surface of the thin film substrate layer with a hard coating liquid and cure it to form a surface hardening layer, thus obtaining a coated reflector; The adhesive comprises the following components by weight: 80-100 parts hydroxy acrylate liquid, 15-35 parts isocyanate curing agent, and 1-3 parts macromolecular antioxidant.

3. The method for preparing a coated reflector according to claim 2, characterized in that: The preparation process of the hydroxyacrylate adhesive is as follows: Mix half of the mass of the mixed solution with the initiator, stir at room temperature under inert gas protection, and then heat up to react. After the reaction is completed, add the remaining mixed solution within 1.5~2.0h, keep the temperature and react to obtain hydroxy acrylate resin.

4. The method for preparing a coated reflector according to claim 2, characterized in that: The preparation process of the isocyanate curing agent is as follows: S1: Anhydrous ethanol and N,N'-bis(2-hydroxyethyl)ethylenediamine were mixed, then hexafluorobutyl methacrylate was added, and the mixture was stirred at room temperature. Then 4-propenoxy-2-hydroxybenzophenone was added, and the mixture was stirred at room temperature to obtain a functionalized polyol. S2: Under inert gas protection, isophorone diisocyanate, functionalized polyol and dibutyltin dilaurate are mixed, heated and stirred to react, and an isocyanate curing agent is obtained.

5. The method for preparing a coated reflector according to claim 2, characterized in that: The preparation process of the macromolecular antioxidant is as follows: Step A: Under inert gas protection, 4-pentenoic acid, functionalized polyol, anhydrous dichloromethane and polymerization inhibitor are mixed and reacted in an ice bath. An activator is added, and then a catalyst is added immediately. The mixture is heated to react and obtain a functionalized antioxidant. Step B: Under inert gas protection, the functionalized antioxidant, N-phenylmaleimide, solvent and initiator are mixed, heated and reacted, and then the temperature is increased to obtain a macromolecular antioxidant.

6. The method for preparing a coated reflector according to claim 3, characterized in that: The mixed solution is obtained by mixing acrylic acid, hydroxyethyl acrylate, butyl acrylate, vinyl acetate and solvent in a mass ratio of (2~5):(16~20):(42~50):(24~32):(70~100).

7. The method for preparing a coated reflector according to claim 4, characterized in that: In S1, the ratio of anhydrous ethanol, N,N'-bis(2-hydroxyethyl)ethylenediamine, hexafluorobutyl methacrylate, and 4-propenoxy-2-hydroxybenzophenone is 150 mL: (46~52) g: (80~90) g: (83~95) g.

8. The method for preparing a coated reflector according to claim 2, characterized in that: In step 2, the metal layer is obtained by using a metal target and depositing it through magnetron sputtering or vacuum evaporation. The metal target material is one of Al, Ag, and Cr.

9. The method for preparing a coated reflector according to claim 8, characterized in that: When magnetron sputtering is used, the process conditions are: under argon atmosphere protection, sputtering power 120~160W, sputtering time 4~8min; When vacuum evaporation is used, the process conditions are as follows: under argon atmosphere protection, evaporation current: 80~100A, evaporation time: 60~240s, evaporation boat temperature: 1000~1200℃.

10. The method for preparing a coated reflector according to claim 2, characterized in that: In step 2, the film is either a PET film or a PC film.